The structure and mechanical properties of Cr-based Cr-Ti alloy films. (14th January 2022) - Liu, Gang; Wang, Miao; Xu, Jianjun; Huang, Min; Wang, Chen; Fu, Yabo; Lin, Changhong; Wu, Jianbo; Levchenko, Vladimir A
Abstract: Previous studies have dealt with Cr and its alloy films that exhibit promising characteristics as surface modification layers for antiwear, anticorrosive, and decorative applications. However, the effect of Ti alloying on the structure and mechanical properties of Cr films has not been studied. This work aimed to the structure and mechanical properties of Cr-Ti alloy films in the Cr-rich side. To this end, pure Cr, Cr-6 at.% Ti, Cr-11 at.% Ti, Cr-16 at.% Ti, and Cr-21 at.% Ti alloy films were prepared by magnetron sputtering, and the structure and mechanical properties of the films were evaluated. The results indicated that all the films exhibited a Cr-based growth with body-centered cubic structure, and increasing the Ti content decreased the (110) orientation growth of Cr basis. Ti alloying increased the hardness of the films, while leaded to a monotonic decrease in the modulus of the films. The first-principles method was employed to demonstrate that the reduced modulus was determined by the Ti alloying degree, rather than the orientation evolution of the films. The analysis of H/E value suggested that the wear resistance of the films was improved by Ti alloying. The mechanical properties of present Cr-Ti alloy films, and other Cr-based alloy films or metallic glasses in publications were compared and discussed. We proposed that Ti alloying is a considerable way to explore advanced mechanical properties of Cr-based alloy films.